Position-dependent cardiovascular response and time-motion analysis during training drills and friendly matches in elite male basketball players - Torres-Ronda, L.; Ric, A.; Llabres-Torres, I.; de las Heras, B.; Schelling i del Alcazar, X. (The Journal of Strength and Conditioning Research, 2016)
The purpose of this study was to measure differences in the cardiovascular workload (heart rate [HR]) and time-motion demands between positional groups, during numerous basketball training drills, and compare the results with in-game competition demands. A convenience sample of 14 top-level professional basketball players from the same club (Spanish First Division, ACB) participated in the study. A total of 146 basketball exercises per player (performed over an 8-week period in 32 team training sessions throughout the competitive season) and 7 friendly matches (FM) played during the preparatory phase were analyzed. The results reveal that HRavg and HRpeak were the highest in FM (158 ± 10; 198 ± 9 b/min, respectively). Time-motion analysis showed 1v1 to be the most demanding drill (53 ± 8 and 46 ± 12 movements per minute for full and half court, respectively). During FM, players performed 33 ± 7 movements per minute. Positional differences exist for both HR and time-motion demands, ranging from moderate to very large for all basketball drills compared with FM. Constraints such as number of players, court size, work-to-rest ratios, and coach intervention are key factors influencing cardiovascular responses and time-motion demands during basketball training sessions. These results demonstrate that systematic monitoring of the physical demands and physiological responses during training and competition can inform and potentially improve coaching strategy, basketball-specific training drills, and ultimately, match performance.